Pyrolysis of Vacuum Residue By Thermal and Catalytic Cracking Using Active Alumina Catalyst - Isnandar Yunanto; Sri Haryati; Muhammad Djoni Bustan (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Vacuum Residue as feedstock derived from Pertamina Refinery Unit III was cracked in a fixed batch reactor under thermal and catalytic with single stage pyrolysis process using active alumina oxide (Al2O3) as a catalyst. The catalytic pyrolysis process carried out at a temperature 450°C in the presence of a varied catalyst to feed ratio 0.5-2.5 w/w% and varied of reaction times 5-30 minutes. While the thermal process performed under same operating conditions without presence the catalyst. The effect of alumina catalyst ratio on quantity and quality of yield product, the effect of operating conditions (reaction times) on yield distribution has been investigated. As a result, the cracked products are liquid, gas and coke residue. The yield of liquid products was dominant, the highest catalyst ratio showed the highest yield of the liquid product reached 63.1 wt% and the lowest yield of coke residue by 24.75 wt%. The highest yield of gas by 23.9 wt% was found at minimum catalyst used by 0.5 wt%